A novel pH‐responsive nanoniosomal emulsion for sustained release of curcumin from a chitosan‐based nanocarrier: Emphasis on the concurrent improvement of loading, sustained release, and apoptosis induction. (30th June 2022) - Haseli, Shabnam; Pourmadadi, Mehrab; Samadi, Amirmasoud; Yazdian, Fatemeh; Abdouss, Majid; Rashedi, Hamid; Navaei‐Nigjeh, Mona
Abstract: Curcumin application as an anti‐cancer drug is faced with several impediments. This study has developed a platform that facilitates the sustained release of curcumin, improves loading efficiency, and anti‐cancer activity. Montmorillonite (MMT) nanoparticles were added to chitosan (CS)‐agarose (Aga) hydrogel and then loaded with curcumin (Cur) to prepare a curcumin‐loaded nanocomposite hydrogel. The loading capacity increased from 63% to 76% by adding MMT nanoparticles to a chitosan‐agarose hydrogel. Loading the fabricated nanocomposite in the nanoniosomal emulsion resulted in sustained release of curcumin under acidic conditions. Release kinetics analysis showed diffusion and erosion are the dominant release mechanisms, indicating non‐fickian (or anomalous) transport based on the Korsmeyer‐Peppas model. FTIR spectra confirmed that all nanocomposite components were present in the fabricated nanocomposite. Besides, XRD results corroborated the amorphous structure of the prepared nanocomposite. Zeta potential results corroborated the stability of the fabricated nanocarrier. Cytotoxicity of the prepared CS‐Aga‐MMT‐Cur on MCF‐7 cells was comparable with that of curcumin‐treated cells ( p < 0.001). Moreover, the percentage of apoptotic cells increased due to the enhanced release profile resulting from the addition of MMT to the hydrogel and the incorporation of the fabricated nanocomposite into the nanoniosomal emulsion. To recapitulate, the current delivery platform improved loading, sustained release, and curcumin anti‐cancer effect. Hence, this platform could be a potential candidate to mitigate cancer therapy restrictions with curcumin.